Hubungan Dukungan Sosial Orang Tua dan Self-Regulated Learning dengan Prestasi Belajar (Indonesian Journal of Guidance and Counseling: Theory and Application, 2022)
Tujuan dari penelitian ini adalah mengetahui hubungan dukungan sosial orang tua dan self-regulated learning dengan prestasi belajar siswa SMP Negeri se-Kecamatan Temanggung. Penelitian adalah penelitian kuantitaif korelasional, subyek terdiri dari 3 sekolah dengan jumlah sampel sebanyak 298 siswa. Hasil analisis menerangkan tingkat dukungan sosial orang tua siswa SMP Negeri se-Kecamatan Temanggung pada kategori tinggi (M=3,36), tingkat self-regulated learning sedang (M=3,19), dan tingkat prestasi belajar yang baik. Hasil dari analisis regresi linier berganda menunjukkan bahwa terdapat hubungan yang signifikan dan positif antara dukungan sosial orang tua dengan prestasi belajar (t=2,660; β=0,186; p<0,05), self-regulated learning berhubungan signifikan dan positif dengan prestasi belajar (t=6,235; β=0,436; p<0,05), dan terdapat hubungan yang signifikan dan positif antara dukungan sosial orang tua dan self-regulated learning dengan prestasi belajar (R=0,586; R2=0,344; F=77,286; p<0,05). Berlandaskan hasil penelitian, mengharapkan guru bimbingan dan konseling dapat memberikan layanan BK terkait bidang belajar untuk dapat memantau prestasi belajar siswa di setiap semester, mempertahankan tingkat dukungan sosial orang tua serta layanan untuk menaikkan self-regulated learning siswa. The purpose of this study is to find out the relationship of social support of parents and self-regulated learning with the learning achievements for students of SMP Negeri in the District of Temanggung. This research is correlation quantitative, the subject consists of 3 schools with a sample number of 298 students. The results of the analysis showed that the level of social support of parents of the students of SMP Negeri in Temanggung District was in the high category (M=3,36), the level of self-regulated learning was average (M=3,19), and level of learning achievement was good. The results of multiple linier regression analysis showed that there is a significant and positive correlation between social support of parents and learning achievement (t=2,660; β=0,186; p<0,05), self-regulated learning has a significant and positive correlation with learning achievement (t=6,235; β=0,436; p<0,05), and there is a significant and positive correlation between social support of parents and self-regulated learning with learning achievement (R=0,586; R2=0,344; F=77,286; p<0,05). Based on the results of the research, it is expected that the teachers of guidance and counseling can provide guidance and counseling services in realm of learning to be able to monitor learning achievement of students in each semester, maintain a level of social support of parents and services to increase of self-regulated learning of students.